Selective Migration and Economic Development: A Generalized Approach - Narcisse Cha'Ngom; Christoph Deuster; Frédéric Docquier; Joël Machado (Institute of Labor Economics (IZA), 2023)
International migration is a selective process that induces ambiguous effects on human capital and economic development in countries of origin. We establish the theoretical micro-foundations of the relationship between selective emigration and human capital accumulation in a multi-country context. We then embed this migration-education nexus into a development accounting framework to quantify the effects of migration on development and inequality. We find that selective emigration stimulates human capital accumulation and the income of those remaining behind in a majority of countries, in particular in the least developed ones. The magnitude of the effect varies according to the level of development, the dyadic structure of migration costs, and the education policy. Emigration significantly reduces cross-country income inequality and the proportion of the world population living in extreme poverty.
Keywords: J61; O15; E24; J24; 330; human capital; migration; selection; brain drain; brain gain; global inequality